Analisis Metafora dalam Berbalas Pantun Upacara Adat Pernikahan Melayu Bengkalis Riau (Pendekatan Semantik) - Sri Rahayu; Puan Zahra Fazliani; Kheysa Aurellta Syahri; Riyanti Riyanti; Diandra Salsabillah Faradiba; Erlian Nisa Harahap; Yaya Efifanya Putri Siregar; Nurul Huda (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of the times and the influence of modernization have also caused a decrease in the use of pantun in everyday life. The younger generation tends to be less interested in studying pantun in depth, thus potentially causing a loss of understanding of the cultural values contained therein. According to (Sung, 2020), pantun is an important part of Malay culture that contains moral values and community identity, so it needs to be preserved and understood comprehensively. The method used in this study is the content analysis method. This method is used to analyze the content or meaning contained in the pantun text. Through this method, researchers identify, classify, and analyze metaphors contained in pantun based on metaphor categories according to Stephen Ulman. The results of the study show that in the reply pantun in the Bengkalis Malay wedding ceremony there are only 2 types of metaphors out of 4 existing types. Namely concrete to abstract metaphors and synesthesia metaphors. The following is the author's description of the research results. From the analysis carried out with a semantic approach based on Stephen Ulman's theory, it was found that the metaphors in Bengkalis Malay wedding pantuns include several types, namely concrete to abstract metaphors, synesthesia metaphors, and a small number of other forms of metaphors. Among these types, concrete to abstract metaphors are the most dominant, because Malay people tend to use real objects or activities to describe abstract life concepts, such as affection, responsibility, commitment, and hope in building a household.